GAMBARAN PENGETAHUAN REMAJA TENTANG KEBENCANAAN COVID-19 - Wiwin Rohmawati; Esri Rusminingsih; Averina Dwie Larensia; Endang Sawitri (Universitas Muhammadiyah Klaten, 2024)
Background:Coronavirus Disease is a new type of disease caused by a virus called Severe Acute Respiratory Syndrome Coronavirus 2 (SARS CoV-2). At the time of the Covid-19 disaster, keeping a distance and prohibiting crowds was quite difficult to apply to teenagers which resulted in Indonesia experiencing an increase in Covid-19 cases due to low knowledge in society, especially among teenagers.Objective: The purpose of this study was to describe the knowledge of adolescents about the Covid-19 disaster in Srago, Pasung, Wedi, Klaten Methods: This research is a quantitative descriptive study. The data collection method uses the Total Sampling method. The sample in this study were 45 respondents. This study used a questionnaire about the Covid-19 disaster which was distributed to adolescents in Srago, Pasung, Wedi, Klaten. Data analysis was performed using univariate analysis. Results: The characteristics of the adolescents who were respondents in this study were mostly 14-16 years old, totaling 17 respondents (38%), dominated by male respondents with a total of 25 respondents (56%), the highest level of education was high school/vocational school education, 19 respondents (42%), some of the respondents' jobs were as students/students, 37 respondents (82%), the source of information about Covid-19 in respondents was from electronic media, 31 respondents (69%). Conclusion: The description of adolescent knowledge about the Covid-19 disaster in Dukuh Srago, Pasung, Wedi, Klaten can be said to be in the sufficient category.